Using the Internet in counseling work during the (Covid 19) Corona pandemic in Anbar province, Iraq - Saleh, Jasim Mohammed; Aljanabi , Ali Razzaq Abbas; Ghaffoori, Anwer Thamer (Technium: Romanian Journal of Applied Sciences and Technology, 2022)
Internet information is constantly updated daily, and every day a new addition in all scientific and agricultural fields, including agricultural productivity and knowledge. This study was conducted to find out the effects of Covid 19 and the benefit of using the Internet with a computer in the field of agricultural extension during the pandemic. This study used the descriptive design and the correlation coefficient to study the relationship between the variables. The study population consisted of all agricultural extension workers in Anbar Governorate (n = 137). Data collected with a questionnaire were subjected to descriptive and Pearson product-moment correlation analysis. Findings indicate that AEWs have access to computers and the internet at work. In addition, indicated that the relationship was significant at level 0.05 between training, and work location with the use of the Internet at work, also the relationship is significant between the use internet and communications at the job and the skills and knowledge in computer and ICT at the level of 0.01. Therefore, it is recommended that extension agencies with Internet sites should be discreet and monitored by government agencies, to prevent the spread of agricultural propaganda sites to sell inferior goods and ideas that are inappropriate and are not supported on the results of scientific research and increase Internet access to agricultural extension staff and posting Innovation to maintain the extension system with confidence and credibility.